Designed membrane protein heterodimers and control of their affinity by binding domain and membrane linker properties. Issue 48 (8th December 2021) - Lan, Chenyang; Stulz, Anja; Barthes, Nicolas P. F.; Lauw, Susan; Salavei, Pavel; Jung, Manfred; Heerklotz, Heiko; Ulbrich, Maximilian H.
Abstract : A pair of designed transmembrane proteins form a dimer at the cell surface, as seen by single molecule imaging. Changes in the linker length or binding domain modulate the 2-dimensional binding affinity. Abstract : Many membrane proteins utilize dimerization to transmit signals across the cell membrane via regulation of the lateral binding affinity. The complexity of natural membrane proteins hampers the understanding of this regulation on a biophysical level. We designed simplified membrane proteins from well-defined soluble dimerization domains with tunable affinities, flexible linkers, and an inert membrane anchor. Live-cell single-molecule imaging demonstrates that their dimerization affinity indeed depends on the strength of their binding domains. We confirm that as predicted, the 2-dimensional affinity increases with the 3-dimensional binding affinity of the binding domains and decreases with linker lengths. Models of extended and coiled linkers delineate an expected range of 2-dimensional affinities, and our observations for proteins with medium binding strength agree well with the models. Our work helps in understanding the function of membrane proteins and has important implications for the design of synthetic receptors.